Bleach. 06, The death trilogy overture - Kubo, Tite (Kubo, Tite. Bleach (VIZ Media), 2005)
Ichigo and Uryû's competition inadvertently results in generating a leviathan of a Hollow whose sheer size is capable of tearing the Soul Reaper's delicately constructed balance to ribbons. Is Ichigo Soul Reaper enough to fell this giant and protect the equilibrium of the universe?